Opsonic and Antibody Responses to Pneumococcal Polysaccharide in Rheumatoid Arthritis Patients Receiving Golimumab Plus Methotrexate. Issue 52 (December 2015) - Migita, Kiyoshi; Akeda, Yukihiro; Akazawa, Manabu; Tohma, Shigeto; Hirano, Fuminori; Ideguchi, Haruko; Matsumura, Ryutaro; Suematsu, Eiichi; Miyamura, Tomoya; Mori, Shunsuke; Fukui, Takahiro; Izumi, Yasumori; et al.
Abstract : Abstract: Vaccination against Streptococcus pneumoniae is recommended for rheumatoid arthritis (RA) patients receiving immunosuppressive treatments. The objective of this study was to evaluate the humoral response to 23-valent pneumococcal polysaccharide vaccination (PPSV23) in RA patients receiving methotrexate (MTX) alone or in combination with a tumor necrosis factor inhibitor, golimumab (GOM). PPSV23 was given to 114 RA patients, who were classified into three groups: RA control (n = 35), MTX alone (n = 55), and GOM + MTX (n = 24). Before and 4 to 6 weeks after vaccination, concentrations of antibodies against pneumococcal serotypes 6B and 23F were measured using an enzyme-linked immunosorbent assay and antibody functionality was determined using a multiplexed opsonophagocytic killing assay, reported as the opsonization index (OI). The IgG concentrations and OIs were both significantly increased in all treatment groups in response to PPSV23 vaccination. In the GOM + MTX group, the IgG responses were lower than those in the MTX alone or control groups, whereas the OI responses were similar to those in the other 2 groups. Furthermore, discrepancies between the IgG and OI responses were found in GOM + MTX group. No severe adverse effect was observed in any treatment groups. OI responses indicate that antibody functionality rather than antibody quantity is important. The similarity of these measurements between all 3 groups suggests that RA patients receiving MTX + GOM still benefit from receiving the PPSV23 vaccination, even though they produce less IgG in response to it. These results can help clinicians to better schedule and evaluate pneumococcal vaccination for RA patients.